2008
DOI: 10.3102/0002831208316951
|View full text |Cite
|
Sign up to set email alerts
|

Developing Citizens: The Impact of Civic Learning Opportunities on Students’ Commitment to Civic Participation

Abstract: This study of 4,057 students from 52 high schools in Chicago finds that a set of specific kinds of civic learning opportunities fosters notable improvements in students’ commitments to civic participation. The study controls for demographic factors, preexisting civic commitments, and academic test scores. Prior large-scale studies that found limited impact from school-based civic education often did not focus on the content and style of the curriculum and instruction. Discussing civic and political issues with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
321
0
28

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 403 publications
(360 citation statements)
references
References 52 publications
11
321
0
28
Order By: Relevance
“…The extent to which individuals are confident about and perceive that they possess politically relevant skills and traits shapes their assessments 6 We recognize that most research finds that playing sports does not influence political engagement in adults or young people (Kahne and Sporte 2008;Verba, Schlozman, and Brady 1995). But scholars do find that athletics can encourage civic engagement when they consider sports as part of a long list of voluntary activities (Marks and Jones 2004;Smith 1999;Walker 2008), though the direct link is tenuous.…”
mentioning
confidence: 99%
“…The extent to which individuals are confident about and perceive that they possess politically relevant skills and traits shapes their assessments 6 We recognize that most research finds that playing sports does not influence political engagement in adults or young people (Kahne and Sporte 2008;Verba, Schlozman, and Brady 1995). But scholars do find that athletics can encourage civic engagement when they consider sports as part of a long list of voluntary activities (Marks and Jones 2004;Smith 1999;Walker 2008), though the direct link is tenuous.…”
mentioning
confidence: 99%
“…For example, Homana Homana, (2009) found that students who participated in open dialogues and discussions in school were more likely to support values and norms related to democratic principle and had higher levels of civic knowledge. Kahne and Sporte Kahne and Sporte (2008) also found an association between students' exposure to democratic classroom practices, such as experiencing an open climate for classroom discussions and studying issues related to students' interests, and greater commitment to civic participation. In addition, other studies have found that exposure to democratic practices in schools are associated with higher levels of student civic knowledge and skills (Littenberg-Tobias, 2015;CIRCLE, 2013;Kahne, Chi & Middaugh, 2006;Kawashima-Ginsberg, 2013;McDevitt & Kiousis, 2006;Syvertesen et al, 2009).…”
Section: Introductionmentioning
confidence: 84%
“…Diferentes estudios demuestran que involucrar a los estudiantes en la deliberación de asuntos ciudadanos tiene efectos positivos y persistentes en una serie de dimensiones del aprendizaje ciudadano, tales como el conocimiento cívico, la tolerancia y el apoyo a los valores democráticos, el sentido de la agenda ciudadana y la comunicación democrática (Beaumont, 2010;Kahne & Sporte, 2008, Torney-Purta, 2002. No obstante, como señalan Carretero, Haste & Bermúdez (2016), dicha valoración de la controversia es particularmente notoria en la educación cívica sustentada en concepciones de democracia como deliberación y como justicia social.…”
Section: La Educación En Derechos Humanos Promoviendo La Discusión Reunclassified